New lives, new challenges: access to intimate partner violence services for portuguese-speaking immigrant women - Sepali Guruge; Margareth S. Zanchetta; Brenda Roche; Stephanie Pedrotti Lucchese (Universidade Federal de Goias, 2019)
Intimate partner violence is a global health issue and the most common form of violence experienced by women. This study explored barriers to accessing help to Intimate partner violence related health services among Portuguese-speaking immigrant women in Toronto, Canada. Exploratory study conducted by a survey and focus group discussions with 12 Portuguese-speaking immigrant women. Results clarify the struggles faced by Portuguese-speaking immigrant women and their pathways to care and help-seeking. Participants reported that the fear of being deported, obtaining evidence of abuse, and lack of language-specific services were the key barriers to seeking help. When available, language-specific community-based services, along with faith and religion, were noted as key factors that supported women's resilience. Nurses who provide care and services to women who are dealing with Intimate partner violence should rethink the scope of their advocacy actions toward addressing these structural barriers by building alliances with organizations to better serve and protect women in such vulnerable situations.